2014
DOI: 10.1007/s10659-014-9506-1
|View full text |Cite
|
Sign up to set email alerts
|

The Directional Dependence of Elastic Stiffness and Compliance Shear Coefficients and Shear Moduli in Cubic Materials

Abstract: The mathematics associated with the representation surfaces for elastic stiffness and compliance shear coefficients and shear moduli for planes in the standard 001-011-111 stereographic triangle for cubic materials is examined as a function of the degree of anisotropy, A = 2c 44 /(c 11 − c 12 ), of the material under consideration. Similarities and differences between the surfaces for the elastic stiffness and compliance shear coefficients and the shear moduli are highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(28 citation statements)
references
References 23 publications
(50 reference statements)
0
24
0
2
Order By: Relevance
“…Elastic constants are created in the relationship between stress and strain and they are dependent on the configuration of crystal lattice, therefore elastic constants are derived from planes in the crystal lattice [ 5 , 6 , 7 , 8 ]. Furthermore, there are several studies on the correspondence of elastic constants and planes/directions such as Ref [ 9 , 10 , 11 ]. Crystallographic planes that are equivalent have similar atomic planar densities.…”
Section: Introductionmentioning
confidence: 99%
“…Elastic constants are created in the relationship between stress and strain and they are dependent on the configuration of crystal lattice, therefore elastic constants are derived from planes in the crystal lattice [ 5 , 6 , 7 , 8 ]. Furthermore, there are several studies on the correspondence of elastic constants and planes/directions such as Ref [ 9 , 10 , 11 ]. Crystallographic planes that are equivalent have similar atomic planar densities.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation results are compared with experimental data calculated using the temperature dependence of the elastic constants c ij . The relation between the elastic constants and the specific shear modulus for a 111 direction is G = (c 11 − c 12 + c 44 )/3 [31,32]. The experimental data for the temperature dependence of the elastic constants is taken from Ref.…”
Section: Discussionmentioning
confidence: 99%
“…The model parameters for Al deformed under quasi-static loading conditions were identified in Rubio et al (2019) and are shown in Table 4. They include the elastic constants of the Al single crystals (Lefebvre, 2006;Knowles and Howie, 2015), the viscoplastic parametersγ 0 and m (Evers et al, 2004), and all the parameters that determine the interactions among dislocations and dislocations and GBs (Rubio et al, 2019). It should be noted that the grain boundaries are not modeled as a single row of elements in each crystal in the bicrystal model.…”
Section: Numerical Modelmentioning
confidence: 99%